2014
DOI: 10.19026/ajas.6.5304
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Cowpea (<em>Vigna unguiculata</em>) Seeds: Incidence of Ethanolic Extract from <em>Balanites aegyptiaca</em>, <em>Melia azedarach</em> and <em>Ocimum gratissimum</em> Leaves on <em>Callosobruchus maculates</em> (Coleptera: Bruchidae)

Abstract: This study aims to evaluate the effect of ethanolic extracts of Balanites aegyptiaca, Melia azedarach and Ocimum gratissimum leaves as bioinsecticide in the preservation of cowpea seeds (Vigna unguiculata) against the pest Callosobruchus maculatus. The extracts were obtained by maceration of leaves powdersin ethanol (95%). These extracts were then used to achieve anti-insecticides tests in jars at doses of 10, 15, 25 and 50% compared to a reference compound (Stargrain). The weevils rearing and some biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In agreement with the findings of the present study, WIPO (2007) also reported that the crude extracts of flowers, flower stalks, leaves and aerial parts of Agapanthus africanus increased germination of radish ( Raphanus sativus L.) seeds when compared with the water control. Furthermore, in a study by Miafo et al (2014) the germination of cowpea seeds was unaffected after treatment with ethanolic leaf extracts of Balanites aegyptiaca (L.) Del., Melia azedarach L. and Ocimum gratissimum L.…”
Section: Discussionmentioning
confidence: 96%
“…In agreement with the findings of the present study, WIPO (2007) also reported that the crude extracts of flowers, flower stalks, leaves and aerial parts of Agapanthus africanus increased germination of radish ( Raphanus sativus L.) seeds when compared with the water control. Furthermore, in a study by Miafo et al (2014) the germination of cowpea seeds was unaffected after treatment with ethanolic leaf extracts of Balanites aegyptiaca (L.) Del., Melia azedarach L. and Ocimum gratissimum L.…”
Section: Discussionmentioning
confidence: 96%